FACTORS THAT OCCUR IN BUYING AND SELLING GHARAR: (CASE STUDY OF DUKU FARMERS IN BUYING AND SELLING THE IJON SYSTEM IN EMBACANG BARU ILIR VILLAGE) - Lia, Dian Wahyu (Reinforce: Journal of Sharia Management, 2025)
This research aims to examine the mechanisms and factors that cause gharar in the practice of buying and selling duku fruit using the ijon system in the village of Embacang Baru Ilir. Using a qualitative approach and involving six informants, including farmers and brokers, the research results show that transactions are conducted orally without written records, while the objects of sale are still in the form of buds or unripe fruit. This situation creates ambiguity regarding the quantity, quality, and delivery time, thereby introducing elements of gharar that are not in line with the principles of buying and selling in Islam. This practice falls into the category of al-muhaqalah, which is a transaction of unclear harvest results that is prohibited as it has the potential to harm one of the parties. The factors causing this are divided into two: internal factors, such as economic needs, greed, and a low understanding of religious teachings, and external factors, including inherited traditions, social environmental influences, and situational conditions. The practice of ijon is seen as a quick solution to obtain funds, even though it violates the principles of justice and certainty in Islam. Therefore, an educational approach is needed to improve farmers' and contractors' understanding of lawful sales and purchases in accordance with Islam. The application of sharia principles to every transaction is believed to encourage the development of a sales system that is more just, transparent, and free of gharar.